Pelatihan dan Pendampingan Mengurus Jenazah di Desa Sidomulyo Kec. Mantup - Musthofa, R. Zainul; Aminah , Siti; Sholikhatin , Yunita; Sholikhah , Zaimatus (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2023)
Humans are the most noble creatures among other creatures, so to take care of the corpse has been regulated in Islamic law with the aim of glorifying it. In the teachings of Islamic law, taking care of the body is fardhu kifayah (the legal status of an activity in Islam that must be carried out, but if it has been done by other Muslims then this obligation is void), so that when in an area there is no one who can take care of the corpse (تجهيز الميت) then one of these areas will sin. Although the law is fard kifayah, it would be better for every Muslim to master his knowledge. It will be very unfortunate if there is not a single community that meets the requirements to abort fardlu kifayah in terms of taking care of the corpse. Therefore, a body care training activity was held by the 20th batch of KKN students at the Sunan Drajat Ds Institute. Sidomulyo, Kec. Mantub, Kab. Lamongan, with the efforts of the youth in the village, especially Karang Taruna, can help take care of the bodies in the area itself, and can also become the successors of their predecessors